2014
DOI: 10.1038/srep04195
|View full text |Cite
|
Sign up to set email alerts
|

Final storage of radioactive cesium by pollucite hydrothermal synthesis

Abstract: The Fukushima nuclear accident has highlighted the importance of finding a better final storage method for radioactive cesium species. Cs is highly soluble in water, and can easily exchange with other alkali ions in zeolites or clays to form stable complexes. However, Cs+ is released from Cs+ complexes into water when surrounded by an excess of water. Pollucite may be the best final storage option for Cs+, but its typical synthesis requires heating to about 1200°C in air. Here, we show that the hydrothermal sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 21 publications
(22 reference statements)
1
16
0
Order By: Relevance
“…In 2014 Yokomori et al . reported their pioneering research on hydrothermal storage of Cs as pollucite 15 , and other research group also studied the feasibility 16 . Whilst examining their work, it has been that clay, which is used as a source of aluminum and silicon, is much more easily dissolved in ethylene glycol than water, under similar temperature and pressure conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014 Yokomori et al . reported their pioneering research on hydrothermal storage of Cs as pollucite 15 , and other research group also studied the feasibility 16 . Whilst examining their work, it has been that clay, which is used as a source of aluminum and silicon, is much more easily dissolved in ethylene glycol than water, under similar temperature and pressure conditions.…”
Section: Resultsmentioning
confidence: 99%
“…During the present research, the following points have been found: cesium can be confined as a stable inorganic crystal, pollucite (CsAlSi 2 O 6 ), by the solvothermal treatment using MMLT and EG; (i) when heated to 350 °C, the maximum pressure reaches 14.8 MPa, and pollucite is easily formed within approximately 10 h, (ii) when heating is stopped at 320 °C, the pressure reaches 6.0 MPa and 8.7 MPa after 9.6 h and 20.6 h, respectively, and the latter condition is preferable, (iii) when heating is stopped at 300 °C, the maximum pressure remains as low as around 2 MPa, and synthesis is not very successful. In the pioneering work 15 by Yokomori et al ., the method is a hydrothermal procedure, and uses water, instead of EG. As different sources (such as bentonite) for Al and Si are used, they also needed other additives such as AlCl 3 .…”
Section: Discussionmentioning
confidence: 99%
“…At present, conversion of various material such as natural zeolites, coal fly ash, smectite clay and chemical regents containing Si, Al and Na to POL or ANA by alkaline hydrothermal treatment method has been reported by many reseachers 3,[6][7][8][9] . However, the optimization of synthesis condition to improve the Cs + removal and the solution stability of obtained product have not been reported.…”
Section: ( )mentioning
confidence: 99%
“…For example, pollucite was hydrothermally synthesized in 240-300 °C for days or hours from clinoptilolite [23]. Therefore, the hydrothermal technology might also have a capability of converting Cs-polluted soil into pollucite which can be used to immobilize Cs into the structure of pollucite in-situ and thus save a huge of amount of solidification basis materials (cement, or glass etc.)…”
Section: Introductionmentioning
confidence: 99%